Children and Adolescents in Virtual Space: Girls’ and Boys’ Behaviour and Attitude to Parental Control - Geležiniene, Renata; Melene, Rita; Vaitkevičiene, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the problem of children’s and adolescents’ activity in virtual space and parental control with regard to this activity. The question is raised what children and adolescents are most often doing in virtual space, for what goals they are using it; it is analysed whether there are any principal differences between boys’ and girls’ activities in virtual space. It is also disclosed how parents control children’s and adolescents’ online activities, how children perceive this control and what teachers think about this. The article reveals peculiarities of boys’ and girls’ activity in virtual space, peculiarities of teachers’ and children’s, adolescents’ attitude to parental control with regard to virtual space.